Green Synthesis of Co3O4/AC Nanocomposite using Bryophyllum pinnatum Leaf Extract for Enhanced Photodegradation of Malachite Green Dye - Sumaiyya Patel; Dinesh Hase; Kanhaiyalal Bhavsar; Vaishali Murade; Gajanan* Pandhare (Journal of Water and Environmental Nanotechnology)
In the present study, the pristine Co3O4 and Co3O4/AC nanocomposites were synthesized by a simple precipitation method using Bryophyllum pinnatum leaf extract, and further examined their photocatalytic degradation efficiency towards malachite green dye. The X-ray Diffraction (XRD) pattern confirmed the cubic and monoclinic phase structure of synthesized Co3O4 nanoparticles. The vibrational modes of as-prepared nanocomposites were analyzed using the Fourier Transform Infrared (FT-IR) technique, and confirmed the presence of bands at 565 cm-1 and 665 cm-1, assigned to Co-O and O-Co-O bonds in the tetrahedral site of the crystal lattice structure. The surface morphological images showed weakly agglomerated irregular nanospheres of Co3O4, and they were successfully immobilized on the surface of activated carbon, ranging between 30-65 nm in diameter. The optical absorption properties were studied, and band gap values were calculated from UV-visible diffuse reflectance spectroscopy (UV-Vis DRS). The green synthesized Co3O4/AC nanocomposite exhibited an excellent degradation ability (96.60%) in comparison with pristine Co3O4 nanoparticles. Thus, the photocatalytic performance of Co3O4/AC nanocomposites revealed the efficient degradation of malachite green dye.